Evaluation of multiple proxies for sea ice variability in Dronning Maud Land - Philippe, Morgane; Tison, Jean-Louis; Dehairs, Frank; Hubbard, Bryn; Pattyn, Frank (2014)
We drilled an ice core at the top of the coastal Derwael Ice Rise, Dronning Maud Land, Antarctica. This 120 meters long ice core should cover about 200-400 years of past accumulation, according to our preliminary results of annual layers identification from optical televiewer-based borehole luminosity. Major ions and water stable isotopes measurements are conducted at high resolution to reveal seasonal variations and improve annual layers identification. At the same time, the potential of sea-ice extent proxies such as sea salt sodium (ssNa), non-sea-salt sulfate (nssSO4) and Methyl Sulfonic Acid (MSA), is investigated. Several studies have shown various positive and negative relationships between these ions and sea ice extent, but very few concerned the region of Dronning Maud Land. Additionnally, NH4, as an indicator of marine biogenic activity, and deuterium excess, as a proxy for moisture source region fluctuations (and potentially sea ice extent) will also be discussed. We found two main results: (a) Na flux is positively correlated to maximum and mean winter (Jan-May) sea ice extent at 30°E. (b) MSA and nssSO4 show similar spatial patterns, different from the Na spatial pattern, presumably more wind-nfluenced info:eu-repo/semantics/nonPublished